2012
DOI: 10.1002/bmb.20572
|View full text |Cite
|
Sign up to set email alerts
|

Immersing undergraduate students in the research experience

Abstract: Molecular cloning skills are an essential component of biological research, yet students often do not receive this training during their undergraduate studies. This can be attributed to the complexities of the cloning process, which may require many weeks of progressive design and experimentation. To address this issue, we incorporated an immersive 12-week undergraduate research experience into an upper-level molecular microbiology course. Students completed two 6-week modules where the entire molecular clonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Given the impact of engaging with undergraduate research on student retention within science programs 21,22 , the long-term value of exposure to research-based learning early in undergraduate education should not be underestimated 34 . focus-group interviews, the ALURE team consistently reported student-learning gains in scientific skills following the completion of ALURE modules 30,31 , with higher gains observed in critical thinking and problem-solving skills when compared to traditional practical modules 32 . Undergraduate research is a high-impact activity that can be of great benefit to students, and the ALURE project has demonstrated that it can be a valuable addition to the instructor's toolkit to bolster student-learning outcomes in transferable skills.…”
Section: Alure: Authentic Large-scale Undergraduate Research Experiencesmentioning
confidence: 97%
See 1 more Smart Citation
“…Given the impact of engaging with undergraduate research on student retention within science programs 21,22 , the long-term value of exposure to research-based learning early in undergraduate education should not be underestimated 34 . focus-group interviews, the ALURE team consistently reported student-learning gains in scientific skills following the completion of ALURE modules 30,31 , with higher gains observed in critical thinking and problem-solving skills when compared to traditional practical modules 32 . Undergraduate research is a high-impact activity that can be of great benefit to students, and the ALURE project has demonstrated that it can be a valuable addition to the instructor's toolkit to bolster student-learning outcomes in transferable skills.…”
Section: Alure: Authentic Large-scale Undergraduate Research Experiencesmentioning
confidence: 97%
“…Following on to third year coursework, students apply techniques in DNA analysis and protein expression in an In Focus laboratory and reporting assessment tasks as part of second and third year ALURE modules 30,31 . The range of learning gains observed following ALURE participation align with graduate attributes desired by STEM employers 8 -improvement in practical competencies for pathology and research laboratories, and generic transferable skills applicable to workplaces both in and out of science [30][31][32] .…”
Section: Alure: Authentic Large-scale Undergraduate Research Experiencesmentioning
confidence: 99%
“…In second year, microbiome samples from 400-500 students are crowd-sourced each semester, and used in an ALURE project investigating microbial composition across different human body sites using culture dependent and independent identification methods 30 . Following on to third year coursework, students apply techniques in DNA analysis and protein expression in an laboratory and reporting assessment tasks as part of second and third year ALURE modules 30,31 . The range of learning gains observed following ALURE participation align with graduate attributes desired by STEM employers 8 improvement in practical competencies for pathology and research laboratories, and generic transferable skills applicable to workplaces both in and out of science [30][31][32] .…”
Section: Alure: Authentic Large-scale Undergraduate Research Experiencesmentioning
confidence: 99%
“…Therefore, IBL involves students gaining competence in inquiry through learning experiences building on their existing knowledge, applying problem solving skills through the use of flexible thinking, and making claims based on evidence. It has further been associated with increased student motivation and interest, deep‐learning, and improved understandings . In the laboratory‐based sciences, IBL has been used for summer vacation based traineeships , and the undergraduate laboratory .…”
Section: Introductionmentioning
confidence: 99%
“…In the laboratory‐based sciences, IBL has been used for summer vacation based traineeships , and the undergraduate laboratory . More specifically in molecular and cell biology settings, IBL often takes the form of bona fide scientific research, involving the generation of a hypothesis, the design and conduct of experiments to produce new knowledge, and reporting the findings in the literature . Importantly, this differs from so‐called “cookbook” practicals where the students repeat a tried and true assay to reach a predetermined conclusion in a process bereft of scientific inquiry .…”
Section: Introductionmentioning
confidence: 99%